(untitled) (Archive of Conferences, 2021)
The article examines the model of distance learning and the didactic conditions of distance learning for disabled students realized through it. The psychological and pedagogical features of teaching disabled students have been studied. The author analyzed the Features of distance learning for children with disabilities and retained intelligence, as well as the solution to the problem of methodological support of distance learning for children with disabilities in the theory and practice of teaching jurisprudence in educational institutions